Early Versus Late Initiation of Dialysis in CKD Stage 5: Time for a Consensus - Emaad M. Abdel-Rahman; Irtiza Hasan; Abdallah S. Abdelrazeq; Ali Rawabdeh; Mei Liu; Nasrollah Ghahramani; David Sheikh-Hamad; Mariana Murea; Pradeep Kadambi; T. Alp Ikizler; Alaa S. Awad (Kidney International Reports)
Chronic kidney disease (CKD), a major global public health problem, emerged as one of the leading causes of death, affecting over 800 million individuals worldwide, with significant burden to patients and their caregivers, and may lead to end-stage kidney disease (ESKD). The decision on optimal initiation of chronic dialysis is a common problem faced by nephrologists, patients, and caregivers due to lack of adequate data. Determining the ideal time to initiate maintenance dialysis for individuals struggling with ESKD has remained a puzzle.Currently, there is no consensus among guidelines as to the best time to initiate dialysis. Discrepancies in guidelines stem from lack of adequate data, necessitating larger randomized controlled trials to fill this major gap and come to a universal acceptance by the nephrology community about the optimal time to initiate dialysis for patients with advanced CKD. The fact that there has been only 1 randomized controlled trial that addressed early versus late dialysis initiation is inadequate to convincingly answer such as critical clinical decision making.In this review, we analyze the available literature and try to come up with recommendations for further studies to guide nephrologists about the best time to initiate dialysis for patients approaching ESKD.